Defining green innovation, its impact, and cycle – a literature analysis - Cisneros Chavira, Pablo; Shamsuzzoha, Ahm; Kuusniemi, Heidi; Jovanovski, Bojan (Elsevier, 2023)
Organizations all over the globe are starting to address environmental-related matters with special emphasis. Several authors believe that for organizations to improve their corporate performance and remain competitive they must minimize pollution and use resources more efficiently. To achieve the previous, green innovations (GIs) ought to be implemented. A lot of knowledge about GIs and everything they entail has been generated over the years. Nevertheless, it is all scattered. There is no consensus among authors and three main concepts (green innovation, sustainable innovation, and eco-friendly innovation) are used interchangeably. Moreover, the advantages of GIs are dispersed within the vast world of information and oftentimes can only be found within articles or books concerning certain specific domains. Likewise, current means for implementing GIs seem to be a completely different topic and unrelated to GIs, as it is hard to find data concerning these in relevant articles. This article is a mere literature review aiming to summarize a topic of a great magnitude such as green innovations and to show what they are, what moves organizations towards them, how can they be achieved, what is being done both in the EU and Finland in that regard, and to and propose a framework to better understand green innovations.
Keywords: Green innovation; Environmental impact; Green mindset; European green policy; Literature analysis; Sustainability; fi=Tietotekniikka|en=Computer Science|; fi=Tuotantotalous|en=Industrial Management|